"Boss Lady": the diagonal networks of African American women photographers from Reconstruction to the Harlem Renaissance - Brady, Emily (2018)
This dissertation argues that the relationships between the first African American women photographers and the various networks they utilised in order to achieve their careers were rooted in notions of respectability, and therefore took on unique 'horizontal,' 'vertical,' and 'diagonal' characteristics. Combining close readings of photographic images with discussion of network theory, I recover the works and lives of neglected African American women artists. Focussing on the period from Reconstruction to the Harlem Renaissance, I discuss the impact of 'horizontal,' 'vertical,' and 'diagonal' networks on these women's careers. By focussing on the foundational years of African American women's camerawork, I am able to chart the changing ideas of the nature of the professional in relation to these networks and shifting artistic ideas. The Introduction establishes my network theory, and contextualises the silence surrounding African American women photographers in the nineteenth and early twentieth centuries. Chapter One explores the importance of marriage as a key vertical network, and how the domestic informed the professional in these women's careers. Finally, Chapter Two introduces the idea of the diagonal network, and how some African American women photographers used professional networks in order to place themselves at the top of their own hierarchies. By combining network theory alongside photographic analysis and biographical information, I seek to rectify the absence of African American women photographers in the American photographic canon and emphasise the innovative and important nature of these women's careers.